Risk factors for death during a resurgence of influenza-A (H1N1) pdm09 in Punjab State in 2013 - Tripurari Kumar; Deepak Bhatia; Pinnaka Venkata Maha Lakshmi; Kayla F Laserson; Jai Prakash Narain; Rajesh Kumar (Wolters Kluwer Medknow Publications, 2017)
Background: In 2013, high mortality from influenza-A (H1N1) pdm09 (pH1N1) was observed in Punjab, India. Objectives: To describe cases and deaths of 2013 pH1N1 positives, to evaluate the high case fatality ratio and risk factors for pH1N1-associated mortality among the hospitalized cases in Punjab for 2013. Methods: A case-control study was conducted and compared those who died from confirmed pH1N1 with those who survived in the hospital between January 1, 2013, and April 30, 2013. Sociodemographic and clinical details were extracted from hospital records and from telephone interviews with controls and next of kin of cases using pretested questionnaires. Logistic regression analysis was performed. Results: A total of 182 laboratory-confirmed pH1N1 cases (99 males and 83 females) were hospitalized in 30 hospitals in Punjab; 42 (23%) patients died. Those who died were significantly more likely to be younger than 50 years of age (adjusted odds ratio [AOR] =10.6, 95% confidence interval [CI] =1.8-21.1), be obese (AOR = 16.7, 95% CI = 1.6-170.7), and have visited more than two health-care facilities before laboratory confirmation (AOR = 25.8, 95% CI = 5.4-121.6). Conclusions: The health-care community should have a high index of suspicion for influenza, and general community should be sensitized about risk factors and to seek medical advice early in the illness.